Dental Students’ Didactic and Psychomotor Skills Performance in Dental Anatomy and Preclinical Operative Dentistry Courses in a Saudi Governmental School - Afnan O. Al-Zain; Adel M. Abdel-Azim; Hisham I. Othman (International Journal of Dentistry, 2021)
Background. Knowledge and psychomotor skills are essential in dental education. The aims were to (1) investigate the correlation between dental students’ didactic and psychomotor skills performance in the dental anatomy and preclinical operative dentistry courses and (2) explore the impact of gender on students’ performance in both courses. Materials and Methods. A retrospective cohort study was performed on dental students’ (164 students; 72 males and 92 females) dental anatomy and preclinical operative courses scores of the same class over 2 years (2018–2020). Didactic and practical scores were collected. The didactic scores included examinations. Practical scores included tooth wax carving for the dental anatomy course and class II cavity preparations and restorations for the preclinical operative. Student’s t-test and ANOVA were used to analyze the difference between the didactic and psychomotor skills scores of both courses and genders. Pearson’s correlation coefficient was used to explore correlations (p<0.05). Results. Moderate, positive, and significant correlations were found between didactic scores in both courses and between dental anatomy’s didactic and psychomotor skills. A weak, positive, and significant correlation existed between the preclinical operative didactic and psychomotor silks (p<0.05). Females’ didactic performance was significantly better than males. Gender had a significant, positive, and moderate correlation in the dental anatomy course, but moderate-weak in preclinical operative (p<0.05). Conclusion. Students’ didactic and psychomotor performance correlations in dental anatomy and preclinical operative courses were positive. The correlation was moderate and weak and varied by course. Gender had a significant impact on student performance and varied by procedure and courses investigated.